Atlantic meridional ocean heat transport at 26° N: impact on subtropical ocean heat content variability - M. Sonnewald; J. J.-M. Hirschi; R. Marsh; E. L. McDonagh; B. A. King (Ocean Science, 2013)
Local climate is significantly affected by changes in the oceanic heat content on a range of timescales. This variability is driven by heat fluxes from both the atmosphere and the ocean. In the Atlantic the meridional overturning circulation is the main contributor to the oceanic meridional heat transport for latitudes south of about 50° N. The RAPID project has been successfully monitoring the Atlantic meridional overturning at 26° N since 2004. This study demonstrates how these data can be used to estimate the variability of the basin-wide ocean heat content in the upper 800 m between 26° and 36° N. Traditionally the atmosphere is seen to dominate the ocean heat content variability. However, previous studies have looked at smaller areas in the Gulf Stream region, finding that the ocean dominates deseasoned fluctuations of ocean heat content, while studies of the whole North Atlantic region suggest that the atmosphere may be dominant. In our study we use a box model to investigate fluctuations of the ocean heat content in the subtropical North Atlantic between 26° and 36° N. The box model approach is validated using 19 yr of high-resolution general circulation model (GCM) data. We find that in both the GCM- and RAPID-based data the ocean heat transport dominates the deseasoned heat content variability, while the atmosphere's impact on the ocean heat content evolution stabilizes after 6 months. We demonstrate that the utility of the RAPID data goes beyond monitoring the overturning circulation at 26° N, and that it can be used to better understand the causes of ocean heat content variability in the North Atlantic. We illustrate this for a recent decrease in ocean heat content which was observed in the North Atlantic in 2009 and 2010. Our results suggest that most of this ocean heat content reduction can be explained by a reduction of the meridional ocean heat transport during this period.